Interaction of Norepinephrine and Glucocorticoids Modulate Inhibition of Principle Cells of Layer II Medial Entorhinal Cortex in Male Mice - Hartner, Jeremiah P.; Schrader, Laura A. (Frontiers in Synaptic Neuroscience, 2018)
Spatial memory processing requires functional interaction between the hippocampus and the medial entorhinal cortex (MEC). The grid cells of the MEC are most abundant in layer II and rely on a complex network of local inhibitory interneurons to generate spatial firing properties. Stress can cause spatial memory deficits in males, but the specific underlying mechanisms affecting the known memory pathways remain unclear. Stress activates both the autonomic nervous system and the hypothalamic-pituitary-adrenal axis to release norepinephrine (NE) and glucocorticoids respectively. Given that adrenergic receptor (AR) and glucocorticoid receptor (GR) expression is abundant in the MEC, both glucocorticoids and NE released in response to stress may have rapid effects on MEC-LII networks. We used whole-cell patch clamp electrophysiology in MEC slice preparations from male mice to test the effects of NE and glucocorticoids on inhibitory synaptic inputs of MEC-LII principal cells. Application of NE (100 M) increased the frequency and amplitude of sIPSCs in approximately 75% of the principal cells tested. Unlike NE, bath application of dexamethasone (1 µM), a synthetic glucocorticoid, or corticosterone (1 µM) the glucocorticoid in rodents, rapidly decreased the frequency of spontaneous spike-evoked inhibitory postsynaptic currents (IPSCs), but not miniature IPSCs in MEC-LII principal cells. Interestingly, pre-treatment with dexamethasone prior to NE application led to an NE-induced increase in sIPSC frequency in all cells tested. This effect was mediated by the α1-AR, as application of an α1-AR agonist, phenylephrine (PHE) yielded the same results, suggesting that a subset of cells in MEC-LII are unresponsive to α1-AR activation without prior activation of GR. We conclude that activation of GRs primes a subset of principal cells that were previously insensitive to NE to become responsive to α1-AR activation in a transcription-independent manner. These findings demonstrate the ability of stress hormones to markedly alter inhibitory signaling within MEC-LII circuits and suggest the intriguing possibility of modulation of network processing upstream of the hippocampus.